Silicone Mold Accuracy in Polyurethane Vacuum Casting. Issue 1 (15th February 2021) - Wortmann, Martin; Frese, Natalie; Brikmann, Johannes; Ehrmann, Andrea; Moritzer, Elmar; Hüsgen, Bruno
Abstract: Vacuum casting of polyurethane (PUR) in silicone molds is used industrially for the production of prototypes and small series as well as in various noncommercial research areas. This includes the reproduction of archeological findings, biological samples or electronic devices. In this study, the authors investigate the molding accuracy of different commercial silicones and PUR casting resins both on microscopic and macroscopic scales. For this, they used a variety of master models to generate silicone rubber casting molds. The resulting PUR castings are investigated by helium ion microscopy, confocal laser scanning microscopy, and optical 3D‐scanning.